Production Process About Alcohol Distillation from Sugar Palm as A Model - Ade Ansari Siregar (International Journal of Mechanical Computational and Manufacturing Research, 2022)
Palm sap is a sweet liquid obtained from the sugar palm plant (Arenga pinnata MEER) by cutting the flower stalk. Generally, palm sap is widely used for the manufacture of brown sugar, fresh drink of palm sap (saguer), vinegar and alcoholic beverages. The potential for palm trees, which are 3 million trees spread throughout North Sumatra. The model planned for the manufacture of this distillation is water distillation, where the collected palm juice is placed in a container that is in direct contact with heating water and then the juice vapor is passed through a pipe connected to it. then condensed through a condenser and the results are accommodated through an alcohol container. A total of 5 liters of palm sap raw material has been mixed with coconut shell charcoal and lime in a ratio of 3: 1 (a good ratio is recommended 150 and 50 grams) is inserted into the heating tank which flows through the top hole by opening the cover, accompanied by filling the water in the heating tank. This water bath can function as a heat regulator, equipped with a thermometer above the water surface so that the temperature of the distillate coming out of the condenser can be known. (7) The result of the distillation process of palm sap with the addition of coconut-lime shell charcoal exceeds the alcohol content of the disinfectant (62%) which has a higher economy. (10) The efficiency of distalization is 82%. equipped with a thermometer above the water surface so that the temperature of the distillate coming out of the condenser can be known. (7) The result of the distillation process of palm sap with the addition of coconut-lime shell charcoal exceeds the alcohol content of the disinfectant (62%) which has a higher economy. (10) The efficiency of distalization is 82%. equipped with a thermometer above the water surface so that the temperature of the distillate coming out of the condenser can be known. (7) The result of the distillation process of palm sap with the addition of coconut-lime shell charcoal exceeds the alcohol content of the disinfectant (62%) which has a higher economy. (10) The efficiency of distalization is 82%.